Assessment of water availability and consumption in the Karkheh River Basin, Iran using remote sensing and geo-statistics - Muthuwatta, Lal P.; Ahmad, Mobin-ud-Din; Bos, M.G.; Rientjes, T.H.M. (Springer, 2010)
This study was conducted to assess water availability and consumption in the Karkheh River Basin in Iran using secondary data and freely available satellite data. Precipitation was estimated using geo-statistical techniques while a Surface Energy Balance approach was selected for evapotranspiration estimation. The spatial distribution of actual evapotranspiration (ETa) for the Karkheh Basin has been estimated by use of 19 cloud free Moderate Resolution Imaging Spectroradiometer (MODIS) images, which cover a complete cropping year from November 2002 to October 2003. ETa estimates were compared to potential crop evapotranspiration (ETp) estimates for two predominantly irrigated wheat areas in Upper and Lower Karkheh. Differences were found to be 12.5% and 11.7% respectively. Results of the ETa and precipitation estimates reveal that for the study period, the Karkheh Basin received 18,507 ? 106m3 as precipitation while ETa is estimated at 16,680 ? 106m3. Estimated outflow from the basin for the study period only is 7.8% of the precipitation and indicates that water is a very scarce resource in the Karkheh basin. The basin has been divided in sub-basins to allow for more detailed analysis and results indicate that water balance closure at sub-basin scale ranges from 7.2% to 0.6% of the precipitation. This suggests that the water balance is sufficiently understood for policy and decision making.